"All the Old Illusions": On Guessing at Being in Crisis. (December 2022) - Sendroiu, Ioana
Models of culture and action argue that crises can be generative of change, with changing contexts setting off reflexivity—a view of crisis as self-evident that is echoed in comparative historical work. Looking to the beginning of the Cold War in Romania and France, this article elaborates two instances when crises did not produce reflexive recognition. This echoes performative approaches that highlight actors needing to interpret crises into being yet underscores that crisis claims nonetheless take place in contexts potentially marked by shifting sociocultural scaffoldings. Rooted in the empirical finding that actors can live through—and be affected by—structural transformations without thinking of themselves as being in crisis, I put forward a conception of crises as unclear as they are taking place. Actors can guess at being or not being in crisis, with no guarantee their guess is fortuitous. Crisis management will be the result of these guesses: some informed, some lucky—and some, indeed, disastrous.